Analysis on memory consumption of mobile application on women safety APP / Nur Farhana Samsudin - Samsudin, Nur Farhana (2020)
The mobile application widely used for multiple purposes in today's world. This also includes the development of the mobile application for safety purposes. However, the effectiveness of the existing safety mobile application is still doubtful. This is because the user has to follow an unnecessary procedure to seek help through the use of the mobile application. This is very time consuming and inefficient to use to help users who need help in situations that can risk their lives. Requesting for help supposed to be quick and effective with the most possible procedure needed to encounter risk situations. Unnecessary series of steps to request help also will affect the memory consumption of the mobile application. It is important to ensure that the mobile application can minimize memory usage of the mobile phone so that this mobile application can be running smoothly and won't crash when requesting for help is needed during a desperate situation. Therefore, this research is to solve all the listed problems by reducing the series of a procedure to get help while submitting the issues related to it. To achieve the objectives of the research, a safety mobile application is aimed to be developed as a prototype that mentioned the above concern and conducted a test to analyze the memory consumption of the mobile application. A series of methodology which involves the qualitative and quantitative methodology applied for this research. Developmental tools of the prototype will be used which include Android Software Development Kit among others. The scope is focusing on women in the society of Malaysia as the research methods are applied by surveys and issues regarding the use of safety mobile applications in society. Finally, the end product of this project is a mobile application prototype that users can use to request help will be developed and the analysis of memory consumption of the mobile application as evidence of concept.